Becoming an Aikidoka: Acculturation and Essentialism in the Practice of Aikido (Revista de Artes Marciales Asiáticas, 2014)
Based on an ethnographic study conducted from 2002-2005 in Canada, this paper argues that the practice of Aikido within a specific community of practitioners does not simply exist as a medium for acquiring martial knowledge, but is also a viable conduit for acculturating or essentializing aspects of Japanese culture and identity. This is made possible in light of the highly embodied and corporeal dimension of Aikido practice, which requires one to develop the necessary dispositions and strategies for the construction of an Aikido habitus. Consequently, the path towards becoming an Aikidoka enables one to potentially embody, in similar but also unique ways, the cultural and moral worldviews that the art seeks to represent within intercultural and transnational spaces.